Integrating OECD Acts into Ukraine’s Regulatory Drafting: Legal Challenges and Prospects - Bogdan Derevyanko; Liudmyla Nikolenko; Olena Bisiuk; Mykhaylo Dutov; Viktoriia Sydorenko (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2026)
Given the OECD’s global influence in shaping responsible business practices and regulatory frameworks, this article focuses on the need for the integration of OECD soft law into Ukrainian legislation. Ukraine has been cooperating with the OECD for over twenty years and holds the status of its prospective member. The OECD evaluated Ukraine, and its conclusions influenced domestic regulatory reforms. In this context, OECD membership is seen as a crucial intermediate step towards Ukraine’s full integration into the EU. Therefore, the aim of the article is to justify the need to integrate the approaches and acts of the OECD into Ukraine’s regulatory drafting as a factor of improving the quality of national legislation and its approximation to EU standards. The research adopts a hermeneutic approach, including hermeneutic, historical-legal, comparative legal, and functional legal methods, to interpret OECD documents and evaluate their relevance to Ukraine’s legal framework. Findings reveal that although OECD acts are not legally binding, their implementation significantly improves transparency, investment attractiveness, and human rights protections. The study highlights Ukraine’s evolving relationship with the OECD, its progress toward membership, and the importance of regulatory drafting in this process. The authors emphasise the importance of due diligence, responsible business conduct, and legal consistency with OECD terminology, advocating for the preservation of the term enterprise in national law. Moreover, the potential legislative risks of repealing the Commercial Code of Ukraine are emphasised. The article concludes that aligning Ukraine’s economic legislation with OECD standards will accelerate its integration into both the OECD and EU. It recommends legislative reforms that adopt OECD principles, enhance state control over compliance, and resist premature abolition of foundational legal concepts critical to international harmonisation.